2021
DOI: 10.4103/jcar.jcar_2_21
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the role of estrogens and androgens in glial tumorigenesis

Abstract: Gliomas are more common in males than in females. Emerging evidence from several studies in vitro and in vivo have shown the role of estrogens and androgens in glial tumorigenesis. In recent times, studies have also shed light on the actions of estrogen receptors, alpha and beta, and androgen receptor. Here, we provide a comprehensive overview of the research hitherto on estrogens and androgens along with an emphasis on their receptors in glioma pathophysiology. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…In this study, the presence of AD is an independent factor associated with a better prognosis in terms of PFS and OS. This finding is supported by previous works that have shown an increase in the growth and invasiveness of glioblastoma cell lines exposed to testosterone [ 17 , 19 , 20 ]. Furthermore, AR activation by its canonical pathway has been associated with the inhibition of the transforming growth factor-β pathway-induced antiproliferative and proapoptotic response in glioblastoma cells [ 12 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the presence of AD is an independent factor associated with a better prognosis in terms of PFS and OS. This finding is supported by previous works that have shown an increase in the growth and invasiveness of glioblastoma cell lines exposed to testosterone [ 17 , 19 , 20 ]. Furthermore, AR activation by its canonical pathway has been associated with the inhibition of the transforming growth factor-β pathway-induced antiproliferative and proapoptotic response in glioblastoma cells [ 12 ].…”
Section: Discussionsupporting
confidence: 90%
“…A higher AR expression in glioblastoma biopsies than in the normal brain has been reported [ 12 , 15 17 ], and AR expression has been associated with the histological grade of glial tumors; a high AR expression is found whenever the tumoral grade increases [ 18 ]. Regarding the role of the AR in glioblastoma, its activation has been associated with increased proliferation of glioblastoma cells and increases in their migration and invasiveness capacity [ 17 , 19 , 20 ]. Furthermore, in vitro and in vivo studies have shown that silencing the AR gene or its pharmacological blockade led to tumoral cell death [ 15 , 16 , 18 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, testosterone-AR-transducing signals may contribute to oncogenesis and tumorigenesis of other malignances, including breast, ovary, bladder, lung, liver, and kidney cancers [ 11 ]. Recently, steroid hormones of estrogen and androgen were reported to possibly be involved in the development of glioblastomas [ 12 ]. Thus, the roles of the AR in tumorigenesis of glioblastomas have attracted a lot of research in wide-ranging investigations [ 13 ].…”
Section: Introductionmentioning
confidence: 99%